Clusterin in the mouse epididymis: possible roles in sperm maturation and capacitation. Issue 6 (December 2017) - Saewu, Arpornrad; Kadunganattil, Suraj; Raghupathy, Riya; Kongmanas, Kessiri; Diaz-Astudillo, Pamela; Hermo, Louis; Tanphaichitr, Nongnuj
Abstract : Clusterin (CLU) is known as an extracellular chaperone for proteins under stress, thus preventing them from aggregation and precipitation. We showed herein that CLU, expressed by principal cells of the mouse caput epididymis, was present in high amounts in the lumen. In the cauda epididymis, CLU bound tightly to the sperm head surface and its amount on total sperm was similar to that in the bathing luminal fluid. In both immotile and motile caudal epididymal sperm, CLU was localized over the entire sperm head except at the convex ridge, although in the motile sperm population, the CLU immunofluorescence pattern was distinctively mottled with a lower intensity. However, when motile sperm became capacitated, CLU was relocalized to the head hook region, with immunofluorescence intensity being higher than that on the non-capacitated counterparts. Under a slightly acidic pH of the epididymal lumen, CLU may chaperone some luminal proteins and deliver them onto the sperm surface. Immunoprecipitation of epididymal fluid proteins indicated that CLU interacted with SED1, an important egg-binding protein present in a high amount in the epididymal lumen. In a number of non-capacitated sperm, fractions of SED1 and CLU co-localized, but after capacitation, SED1 and CLU dissociated from one another. While CLU moved to the sperm head hook, SED1 translocated to the head convex ridge, the egg-binding site. Overall, CLU localization patterns can serve as biomarkers of immotile sperm, and non-capacitated and capacitated sperm in mice. The chaperone role of CLU may also be important for sperm maturation and capacitation.